Comparison of Estimated Blood Loss between Tranexamic Acid and Control in Women Undergoing Elective Cesarean Section - Javeria Masood, Zartaj Hayat, Nadia Ahmed, Robina Jabeen, Nazish Shifa, Faiza Masud, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tranexamic acid is being utilized related to uterotonic agents to treat hemorrhage post-delivery. Evidence suggests that tranexamic acid may reduce bleeding and resultant chances of postpartum hemorrhage. However, limited data is available on the prophylactic utilization of tranexamic acid in local women undergoing elective lower segment cesarean section. This study aimed to compare reduction in mean blood loss between control and tranexamic acid group during and after elective lower segment cesarean section. Methodology: This randomized controlled trial was done in a period of 6 months i.e. 17th December 2018 to 17th June 2019 in the Department of Gynecology and Obstetrics, FUI, Fauji Foundation Hospital, Rawalpindi. Sixty women were randomly equally allocated to Group A (tranexamic acid) and Group B (non-tranexamic acid). Patients were given tranexamic acid 1gm intravenous 15 minutes before skin incision. Hemoglobin and hematocrit levels were estimated on second post cesarean day (before discharge) as well to measure outcome i.e. estimated blood loss. Results: In tranexamic acid group, mean estimated blood loss following elective lower segment cesarean section found to be 301.66±64.97 ml while in non-tranexamic acid group it was 433.33±137.29 ml. The significant (P<0.05) difference was noted. Conclusion: The mean estimated blood loss reduced significantly in patients who were given tranexamic acid before elective lower segment cesarean section than those who were not given tranexamic acid. Keywords: Postpartum hemorrhage, tranexamic acid, elective lower segment cesarean section (E:-LSCS)